2020
DOI: 10.3892/mmr.2020.11329
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of 2019 novel coronavirus pneumonia in Zhejiang province, China

Abstract: Since december 2019, an increasing number of cases associated with the 2019 novel coronavirus (2019-ncoV) have emerged in Wuhan, china, which has resulted in a rapid outbreak in china and worldwide. The present study aimed to describe the clinical, laboratory and radiological characteristics of 2019-ncoV pneumonia (ncP) in Zhejiang province, outside of Wuhan. a total of 74 patients with 2019-ncoV were continuously enrolled between January 22 and March 2, 2020 at Zhejiang Hospital. Diagnosis was confirmed at Zh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Since the first outbreak of the coronavirus disease 2019(COVID-19) in late 2019 in Wuhan, Hubei, China ( Zhang et al, 2020 ; Chen et al, 2020 ), this highly contagious respiratory syndrome had spread quickly to become the most serious issue to public health globally ( Zhou et al ). As of March 16, 2021, the WHO reported that more than 119.9 billion cases have been confirmed worldwide and more than 2.65 million people died (2020a).…”
Section: Introductionmentioning
confidence: 99%
“…Since the first outbreak of the coronavirus disease 2019(COVID-19) in late 2019 in Wuhan, Hubei, China ( Zhang et al, 2020 ; Chen et al, 2020 ), this highly contagious respiratory syndrome had spread quickly to become the most serious issue to public health globally ( Zhou et al ). As of March 16, 2021, the WHO reported that more than 119.9 billion cases have been confirmed worldwide and more than 2.65 million people died (2020a).…”
Section: Introductionmentioning
confidence: 99%
“…The daily reported epidemiological data of these regions are collected through the websites of the Health Commissions or from the literature (Cheng et al. 2020b ; Liu et al. 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Mouse model of asthma is characterized with AAI developed with i.p OVA sensitization and i.n challenge with OVA in BALB/c mice. This model is characterized by airway inflammation associated with increased type 2 lymphocytes infiltration, eosinophils, alveolar epithelial barrier damage, and mucus secretion by epithelial goblet cells, [2,15,16,32,33] however, the inflammatory manifestations in the gut in not well studied. As observed in several previous studies highlighted the importance of Th2 responses in both gut and lung, we first intend to observe the type of inflammation in the gut and lung at prechallenge and post-challenge conditions during the development of AAI in mouse model of asthma.…”
Section: Discussionmentioning
confidence: 99%